Quality and Fatty Acid Composition of Lipids from Head of Indian Mackerel (Rastreliger kanagurta) and Tigertooth Croaker (Otolithes ruber) - Elavarasan, Krishnamoorthy; Kumar, Anuj; Tejpal, C. S.; Kumar, K. Sathish; Uchoi, Devananda; Ninan, George; Zynudheen, A. A. (Fishery Technology, 2017)
Fish processing discards contain valuable nutrientssuch as proteins, lipids and minerals. The lipid frommackerel and croaker head extracted by alkalisolubilization was recovered and characterized forquality parameters such as peroxide value (PV), freefatty acid (FFA), thiobarbituric acid reactive substances(TBARS) and fatty acid composition. PV, FFAand TBARS values of lipids recovered from head ofmackerel was higher than that of croaker. Bothmackerel and croaker head lipids had higheramount of saturated fatty acids (SFA) andmonounsaturated fatty acids (MUFA) and loweramount of polyunsatuarated fatty acids (PUFA)compared to fatty acids from muscle of the samefishes. Mackerel head lipids had higher PUFAcontent (30.81%) than that of croaker (18.71%). TheSFA content was dominated by palmitic acid whilethe MUFA content was dominated by palmitoleicacid. Docosahexaenoic acid (DHA; C22: 6 Ï‰3) andEicosapentaenoic acid (EPA; C 20: 5 Ï‰3) were thedominant PUFA in both the fish-head lipids. Thestudy revealed the fish head waste as a potentialsource of Ï‰-3 fatty acids which can be recovered byalkali solubilization process.